Pengaruh Family’s Recorded Voice Terhadap Tingkat Kesadaran Pasien dengan Cedera Kepala di RSUD Ulin Banjarmasin - Maulidya Septiany; Cecep Eli Kosasih; Urip Rahayu (FORIKES, 2024)
Head injuries can cause cognitive and physical damage, making them one of the main causes of death and disability. Providing a stimulus as early as possible is very important to activate the ascending reticular activating system so that it will increase awareness which makes a person aware of themselves and their environment, so that the sequelae experienced by the patient can be minimized. This study aimed to analyze the effect of family's recorded voice on consciousness in patients with head injuries at Ulin Hospital, Banjarmasin. This research implemented a pretest-posttest design with control group. This research involved 50 respondents who were divided into two groups, namely the intervention group which received auditory stimulation in the form of family's recorded voices for 5 days and the control group which received standard therapy. Assessment of the level of consciousness was carried out before stimulation (third day of treatment) and after stimulation (seventh day of treatment). The data obtained were analyzed using 2 tests, namely the Wilcoxon test and the Mann-Whitney test. This research shows a value of p = 000. Furthermore, it is concluded that there is an influence of the family's recorded voice on the level of consciousness in patients with head injuries at Ulin Regional Hospital, Banjarmasin.Keywords: head injury; auditory stimulation; level of awareness; loss of consciousness ABSTRAK Cedera kepala dapat menimbulkan kerusakan kognitif dan fisik, sehingga menjadi salah satu penyebab kematian dan kecatatan utama. Pemberian stimulus sedini mungkin sangatlah penting untuk mengaktivasi ascending reticular activating system sehingga akan meningkatkan kesadaran yang membuat seseorang sadar terhadap diri dan lingkungannya, sehingga gejala sisa yang akan dialami oleh pasien dapat diminimalisir. Penelitian ini bertujuan untuk menganalisis pengaruh family’s recorded voice terhadap kesadaran pada pasien dengan cedera kepala di RSUD Ulin Banjarmasin. Penelitian ini menerapkan rancangan pretest-posttest with control group. Penelitian ini melibatkan 50 responden yang terbagi dalam dua kelompok yaitu kelompok intervensi yang mendapatkan stimulasi auditori berupa family’s recorded voice selama 5 hari dan kelompok kontrol yang mendapatkan terapi standar. Penilaian tingkat kesadaran dilakukan sebelum diberikan stimulasi (hari ketiga perawatan) dan setelah stimulasi (hari ketujuh perawatan). Data yang diperoleh dianalisis menggunakan menggunakan 2 uji yaitu menggunakan uji Wilcoxon dan uji Mann-Whitney. Penelitian ini menunjukkan nilai p = 000. Selanjutnya disimpulkan bahwa terdapat pengaruh family’s recorded voice terhadap tingkat kesadaran pada pada pasien dengan cedera kepala di RSUD Ulin BanjarmasinKeywords: cedera kepala; stimulasi auditori; tingkat kesadaran; penurunan kesadaran